2000
DOI: 10.1080/00034980050006410
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey to analyse the risk factors associated with human cystic echinococcosis in an endemic area of mid-Wales

Abstract: In mid-Wales, the prevalence of cystic echinococcosis (hydatid disease) in humans and other animals has been well documented. A cross-sectional study was therefore undertaken to examine the associated demographic and environmental risk factors for the disease in humans, in Powys, mid-Wales. Overall, 223 fully completed questionnaires were returned from a postal survey. Eighteen of the respondents had been treated for cystic echinococcosis (CE). No significant association was found between many of the well-esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…These two practices combined with the uncontrolled roaming of dogs and dissemination of Eg eggs in fields, pastures and water resources, constitute a major risk factor for human disease. This finding corroborates the findings of other studies undertaken in Morocco, namely those undertaken in the region of Loukkos [ 35 , 54 ] and in the region of Khenifra [ 34 ], as well as others studies undertaken in Uruguay [ 55 ], Jordan [ 56 ], Argentina [ 57 ] China [ 36 ] and Tunisia [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These two practices combined with the uncontrolled roaming of dogs and dissemination of Eg eggs in fields, pastures and water resources, constitute a major risk factor for human disease. This finding corroborates the findings of other studies undertaken in Morocco, namely those undertaken in the region of Loukkos [ 35 , 54 ] and in the region of Khenifra [ 34 ], as well as others studies undertaken in Uruguay [ 55 ], Jordan [ 56 ], Argentina [ 57 ] China [ 36 ] and Tunisia [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…This finding has been observed in various other regions of Morocco by Mahjour et al [ 40 ] and Ouhelli et al [ 41 ] in different areas, by Achemlal [ 27 ] in the region of Tetouan, by Tabyaoui [ 42 ] in the region of Azrou and El Mansouri et al [ 43 ] in the region of Rabat. This was also observed by authors in other countries including Wales [ 44 ], Iraq [ 45 ], Jordan [ 46 ], in Turkey [ 47 ], China [ 36 , 37 ] and Tunisia [ 48 ].…”
Section: Discussionsupporting
confidence: 77%
“…So far, the evidence on dog owning-related risk factors for CE transmission is still uncertain and the studies produced few contradictory results. Some studies even showed no positive correlation between dog ownership and CE infections [ 29 , 36 38 ] while other studies showed positive correlations [ 30 , 31 , 33 ]. Tamarozziet al (2019) emphasized that CE is more “soil-transmitted” than a “food-borne” infection, acquired through a “hand-to-mouth” mechanism [ 3 , 25 , 29 ].…”
Section: Discussionmentioning
confidence: 99%